ASSISTED SUICIDE IN JOJO MOYES’ ME BEFORE YOU - Ria Lestari (LINGUA LITERA : journal of english linguistics and literature, 2020)
ABSTRACT This research aims to analyze Assisted Suicide that is portrayed in a novel entitled Me Before You by Jojo Moyes. It tells about the male main character, Traynor, who chooses to end his life through assisted suicide because he is paralyzed as a result of a motorcycle accident. There are two questions to discuss in this research; the causes of assisted suicide and the causes of objectification. This research uses existentialism theory by JeanPaul Sartre.There are some concepts of theory i.e Freedom, The look, and The body that help this research to describe the causes of assisted suicide and the causes of objectification. The research method used by the writer was the qualitative research method. The result of this research showed that the cause of assisted suicide is the excessive freedom to choose to be free from physical pain and emotional pain. Then, the cause of objectification is the existence of the Other, such as The Look and The body that affect Traynor’s existence when people around him try to change his mind not to commit suicide.